2023
DOI: 10.1039/d3tb01660a
|View full text |Cite
|
Sign up to set email alerts
|

Wool keratin/zeolitic imidazolate framework-8 composite shape memory sponge with synergistic hemostatic performance for rapid hemorrhage control

Feng Sang,
Xiao Yang,
Jiahui Hao
et al.

Abstract: By combining the keratin and ZIF-8 particles, the problems of the poor mechanical properties and lack of antibacterial effect of the keratin sponge was solved. The released by Zn2+ form ZIF-8 acted as crosslinker to form Zn-S with sulfhydryl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…A characteristic peak at 660 cm –1 was observed in the keratin powder, which was due to the stretching vibration of C–S . Besides, the presence of amide I (1600–1700 cm –1 ), II (1480–1580 cm –1 ), and III (1220–1330 cm –1 ) peaks could be observed in both keratin powders, which is an important indicator for determining the secondary structure of proteins . To further verify the composition of the extracted keratin, we conducted amino acid composition analysis experiments.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A characteristic peak at 660 cm –1 was observed in the keratin powder, which was due to the stretching vibration of C–S . Besides, the presence of amide I (1600–1700 cm –1 ), II (1480–1580 cm –1 ), and III (1220–1330 cm –1 ) peaks could be observed in both keratin powders, which is an important indicator for determining the secondary structure of proteins . To further verify the composition of the extracted keratin, we conducted amino acid composition analysis experiments.…”
Section: Results and Discussionmentioning
confidence: 99%
“…29 Besides, the presence of amide I (1600−1700 cm −1 ), II (1480−1580 cm −1 ), and III (1220−1330 cm −1 ) 30 peaks could be observed in both keratin powders, which is an important indicator for determining the secondary structure of proteins. 31 To further verify the composition of the extracted keratin, we conducted amino acid composition analysis experiments. The results showed that keratin contains 17 types of amino acids, with cysteine content accounting for 7.36%, indicating that keratin contains a higher amount of thiol groups for cross-linking reactions (Table S1).…”
Section: Extraction Of Keratin and Preparation Ofmentioning
confidence: 99%